Implementation of Pancasila Democracy in Temanggung District in the General Election - Sistyawan, Dwanda Julisa; Gashimov, Elchin (Yayasan Ilomata, 2024)
This research examines the implementation of Pancasila democracy during general elections in Temanggung District, focusing on public participation and trust in the electoral process. The study aims to analyze the application of Pancasila values in the democratic process, assess public involvement and trust, identify obstacles, and propose solutions. Normative legal research methods and a conceptual approach were employed to analyze the implementation of Pancasila democracy. Findings indicate the need to optimize measures to achieve democracy aligned with Pancasila principles, including enhancing public trust and awareness of the collective goal of elections. Residents of Temanggung Regency demonstrate a high level of trust in community participation as a manifestation of Pancasila democracy. The study identifies strengths and weaknesses in implementing Pancasila democracy, highlighting obstacles like low awareness and limited engagement. Proposed solutions include increasing public awareness, enhancing voter education, and fostering community engagement to strengthen democratic values. Addressing challenges such as voter education, political apathy, and distrust in the electoral system is crucial for a robust Pancasila democracy. Enhancing public participation, trust, and awareness is essential for upholding Pancasila democracy in Temanggung District.